Karakterisasi Kualitas Biobriket Campuran Tempurung Kelapa dan Sekam Padi dengan Variasi Perekat dan Ukuran Serbuk - Ropiudin - Ropiudin (Program Studi Teknik Pertanian, Fakultas Pertanian, Universitas Jenderal Soedirman, 2022)
Biobriquette is an alternative fuel that is solid and comes from waste or the remnants of organic matter that has undergone a compression process with a certain pressure. This biobriquette is a mixture of coconut shell and rice husk biobriquettes with variations in adhesives and variations in powder sizes. The purpose of this study was to determine the optimal adhesive content of tapioca flour in the process of making biobriquettes from coconut shells and rice husks, to determine the effect of powder size on the quality of the resulting biobriquettes and to determine the best combination of adhesive content and powder size to produce biobriquettes. Making biobriquettes using 30, 40 and 50% adhesive with powder sizes of 20, 40, 60 mesh. The experimental design method was carried out by Completely Randomized Design or RAL with 2 factors, namely variations in adhesives and variations in powder sizes. Data analysis was performed by ANOVA test and continued with DMRT. The results obtained are, adhesive variations have no significant effect on the rate of combustion, while powder size has no significant effect on moisture content. The moisture content obtained is around (3.2-6%) which meets SNI, while the density that does not meet SNI is biobriquettes with a powder size of 20 mesh.